DEVELOPMENT OF LOW-COST CLINICAL BLOOD PRESSURE DATA RECORDING UNIT WITH HIGH SAMPLING RATE - Ega, Adindra Vickar; Ginanjar, Gigin; Tantokusumo, Timotius Christopher (National Standardization Agency of Indonesia, 2023)
This paper discusses the improvement of blood pressure recording unit in sampling rate and cost efficiency from the previous recorder using Arduino and PLX-DAQ. In order to increase the sampling rate, the NI-myDAQ device and LabVIEW program were used. The recording unit was able to record the blood pressure samples with the sampling rate 200000 samples/second which complies with the ISO/TS 81060-5 : 2019 with relatively low-cost. However, further development in recording Korotkoff sounds, determining systolic, diastolic, and mean arterial blood pressures are required.Keywords: blood pressure, recording unit, ISO/TS 81060-5, sampling rate, low-cost